(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Nurses Notes (NN) is an important record maintained by nurses as part of the care provided to patients. It also serves as a legal document in the field of patient care. Generally nursing institutions in India use their own formats to maintain patient care records by their students, resulting into a variety of different NN formats across nursing institutions in India. This scenario indicates a research gap towards a standardization of NN format across India.This research addresses identified gap through the development of a standard NN format for nursing institutions in India. Material and Methods: Researchers conducted a review of existing NN formats used by different nursing institutions across India. An initial draft of Comprehensive Nurses Notes (CNN) format was then prepared following synthesis research approach. CNN was then optimized as per feedback received from 17 experts (nursing teachers having minimum of 10 years of teaching experience) following purposive sampling method. The optimized CNN (OCNN) draft then used as a structured questionnaire administered through online method to collect feedback from 100 experts across India following random sampling method. This resulted into design of standardized NN format for nursing institutions across India. Approval was taken from institutional research review committee and informed consent was taken from the participants.Result: CNN was optimized through Content Validity Ratio (CVR) analysis with 0.42 as critical value as per the size of expert panel, resulting into OCNN. Validity of OCNN analyzed through Content Validity (S-CVI/Ave as 0.88, S-CVI/UA as 0.964 and critical values as 0.78) and Face Validity. Its reliability was tested through using test-retest method. Conclusion: The result provides a standardized Nurses Notes format for nursing institutions across India. It will help to bring uniformity in NN management leading to development of India specific NN protocol towards an electronic version of NN.